How Do Career Aspirations Benefit Organizations? The Mediating Roles of the Proactive and Relational Aspects of Contemporary Work - Baroudi, Sabrine El; Khapova, Svetlana N.; Fleisher, Chen; Jansen, Paul G. W. (Frontiers in Psychology, 2018)
This paper examines how employees’ career aspirations benefit organizations, i.e., contribute to strengthening organizational capabilities and connections, by means of two aspects of contemporary work: proactive and relational. Data were collected from alumni of a public university in Amsterdam, the Netherlands, in two waves with a one-year time lag. The results showed that employees with career aspirations strengthen: a) organizational capabilities; and b) organizational connections through their instrumental and psychosocial relationships. Interestingly, although employees’ career aspirations were positively associated with taking charge, we did not find that taking charge mediates the relationship between career aspirations and employees’ individual contributions to organizational capabilities. This study is the first to examine how individual career aspirations benefit organizations, and it discusses the results in light of their novel contributions to theory and practice.